Globalization, PyMEs and the emergence of Local Innovation Systems - Hernández Medina, Carlos Alberto (2020)
Abstract: The influence of Globalization process on emergence of new development paradigms at global, regional, national and local level is analyzed. Global changes have generated new forms of knowledge management, the production and commercialization relationships have varied, and new interrelations in the lattice of the social life arose. Knowledge management and training become fundamental occupations at all society levels. These new behaviours in productive and services activity forced to the creation of Local Innovation Systems to front the challenges from the new global situation to territory level.